PENGEMBANGAN MEDIA VIDEO ANIMASI MENGGUNAKAN POWTOON PADA TEMA DAERAH TEMPAT TINGGALKU SUBTEMA KEUNIKKAN DERAH TEMPAT TINGGALKU - Sri Ade Tia Widia Ningsih; Ratih Purnamasari; Dita Destiana (STKIP Subang, 2023)
This researchaims to detremine the development and fesibility of animated video media using Powtoon on the theme of the area where I live, sub-theme, the uniqueness of area where I live. This reserch uses an R&D (Research and development) research approach using the ADDIE model, there are five stages of analysis, design, implementation, evaluation. The subject of this research were class IVA student at Ciawi 23 state elementary school, consisting of 26 students. This research was conducted in the even semester of the 2022/2023 academic year. In this research, the instruments used consisted of validation sheets from media experts, language experts, material experts, student response questionnaire results, and teacher response questionnaire results. This is proven by the media validation results which obtained a percentage of 88%, language experts obtained a precentage of 90%, and material experts obtained a precentage of 88%.